4
$\begingroup$

If $x,y,z>0$, prove that: $\frac{x}{y+z}+\frac{y}{x+z}+\frac{z}{x+y}\ge \sqrt{2}\sqrt{2-\frac{7xyz}{(x+y)(y+z)(x+z)}}$

The solution goes as follows:

$a=\frac{x}{y+z}$, $b=\frac{y}{z+x}$, $c=\frac{z}{x+y}$. We can see that:

$ab+bc+ac+2abc=1$

It's enough if: $(a+b+c)^2\ge 4-14abc$

$(a+b+c)^2\ge 4(ab+bc+ab+2abc)-14abc$

From Schur it is enough if: $6abc\ge\frac{9abc}{a+b+c}$ which is true from Nesbit.

Could you please provide a more intuitive and easier approach?

$\endgroup$
12
  • 1
    $\begingroup$ So are you facing difficulty on how they got $ab+bc+ca+2abc=1$?there is anice proof for that $\endgroup$ Mar 6 at 17:40
  • 1
    $\begingroup$ @AlbusDumbledore actually that's exactly what is giving me difficulties, I can't prove it $\endgroup$ Mar 6 at 17:43
  • 3
    $\begingroup$ @AlbusDumbledore sorry for having deleted the chat, it's the first time I created a chat and I thought I had done something wrong. Sorry about that. Thank you so much for your response, your reasoning is brilliant, I have understood it implicitly. Have a great day $\endgroup$ Mar 6 at 18:53
  • 1
    $\begingroup$ @MichaelBlane We can get $a + b + c \ge \frac{3}{2}$ from $ab+bc+ac+2abc=1$ without using Nesbitt. Indeed, from $(a + b + c)^2 \ge 3(ab + bc + ca)$ and $a + b + c \ge 3\sqrt[3]{abc}$, we can easy get $a + b + c \ge \frac{3}{2}$. $\endgroup$
    – River Li
    Mar 9 at 2:04
  • 1
    $\begingroup$ @V.S.e.H. I think it is fine as comment. From $(a + b + c)^2 \ge 3(ab + bc + ca)$ and $a + b + c \ge 3\sqrt[3]{abc}$, we have $\frac{(a + b + c)^2}{3} + 2 \cdot (\frac{a + b + c}{3})^3 \ge ab + bc + ca + 2abc = 1$ which results in $a + b + c \ge 3/2$. $\endgroup$
    – River Li
    Mar 14 at 15:13
1
$\begingroup$

if $x,y,z > 0 $, say $a = \frac{x}{y+z} , b=\frac{y}{x+z} , c=\frac{z}{x+y} $ then we'll proof that $$(a+b+c)^2 \ge 4 - 14\cdot a \cdot b \cdot c $$ $(a+b+c)^2 = a^2+2.a.b+b^2+2.a.c+2.b.c+c^2 = a^2+b^2+c^2+2(a.b+b.c+a.c) $

as you said $a.b+a.c+b.c+2.a.b.c = 1$

$a^2+b^2+c^2 +2(1-2.a.b.c) \ge 4 - 14.a.b.c $

$ a^2+b^2+c^2 +2 - 4.a.b.c \ge 4 - 14.a.b.c $

$ a^2+b^2+c^2 +10.a.b.c \ge 2 $

since $x,y,z > 0 $ means that $x$ or $y$ or $z$ are positive numbers, their lowest value is $ 0 + 10^{-n} $ and since our inequality speaks also minimum value, we can get the result by assuming the minimum value of $x,y,z$ there

for the simplest case scenario, this happens when $ x= y= z$ at the lowest level

$ x^2/(z+y)^2+y^2/(z+x)^2+z^2/(y+x)^2 + (10.x.y.z)/((y+x)(z+x)(z+y)) \ge 2 $

so if i say $x=y=z$, the result is $2$ this means that even if $x , y , z$ was $ < 0 $ our inequality would still be greater than 2

$\endgroup$
1
$\begingroup$

Well it's an attempt to delete the square root .

My only idea is to use Bernoulli's inequality and play with the coefficient $\sqrt{2}$.We have :

$$\sqrt{2}\sqrt{2-\frac{7xyz}{(x+y)(y+z)(x+z)}}\leq \sqrt{\alpha}\Big(1+\frac{1}{2}\Big(\frac{4}{\alpha}-1-\frac{14}{\alpha}\frac{xyz}{(x+y)(y+z)(x+z)}\Big)\Big)$$

Remains to show (using the OP's substitution) when:

$$ \sqrt{\alpha}\Big(1+\frac{1}{2}\Big(\frac{4}{\alpha}-1-\frac{14}{\alpha}abc\Big)\Big)\leq a+b+c$$

Wich seems to be easier I think.

The last inequality is equivalent to :

$$\frac{y}{2}+\frac{2}{y}\leq a+b+c+\frac{7}{y}abc$$

With $y^2=\alpha$ so now a bit of algebra to get :

$$y^2+4\leq 2y(a+b+c)+14abc$$

Now putting $y=a+b+c$ we get the inequality of the OP.

The end is the same as the OP.

$\endgroup$
11
  • $\begingroup$ @RiverLi Good point but If you read carefully I say that it works only for some values. $\endgroup$
    – Erik Satie
    Mar 14 at 8:28
  • $\begingroup$ @RiverLi Well there is a typo ! $\endgroup$
    – Erik Satie
    Mar 14 at 8:38
  • $\begingroup$ @RiverLi Well you're right I forgot that and maybe it's a bad idea .But I don't see better than the OP's proof ! $\endgroup$
    – Erik Satie
    Mar 14 at 9:44
  • $\begingroup$ @RiverLi I think there is something wrong can you tell me where ? $\endgroup$
    – Erik Satie
    Mar 14 at 10:17
  • $\begingroup$ @RiverLi So do you think it's a nice refinement ? $\endgroup$
    – Erik Satie
    Mar 16 at 10:20
1
+25
$\begingroup$

Version of 01.04.2021.

Since the task is homogenious, one may denote $$s=x+y+z=3,\quad r=xy+yz+zx,\quad p=xyz,\tag1$$ wherein $$r\le\dfrac13s^2=3,\quad p\le\dfrac1{27}s^3=1. \tag2$$ At the same time, $$p=(3-u)v,\quad r=(3-u)u+v,\tag3$$ where $$u=x+y\in[0,3],\quad v=xy\in\left[0,\dfrac{u^2}4\right].\tag4$$

The given inequality takes the forms of $$4\big(x(s-y)(s-z)+y(s-z)(s-x)+z(s-x)(s-y)\big)^2$$ $$ \ge \big(16(s-x)(s-y)(s-z)-56xyz\big)(s-x)(s-y)(s-z)$$ $$ = \big(4(s-x)(s-y)(s-z)-7xyz\big)^2 -49(xyz)^2,$$ or $$4(s^3-2sr+3p)^2+49p^2\ge (4sr-11p)^2,\tag5$$ wherein, taking in accouint $(1)-(4),$

$$4(s^3-2sr+3p)^2+49p^2-(4sr-11p)^2$$ $$=4(27-6r+3p)^2+49p^2-(12r-11p)^2$$ $$=12(-108r+10pr-3p^2+54p+243)=12f(u,v),$$ $$f(u,v)=243-324u+108u^2+54v+36uv-60u^2v+10u^3v+3v^2+8uv^2-3u^2v^2,$$ $$f'_v(u,v)=54+36u-60u^2+10u^3+6v+16uv-6u^2v.$$ Then at the bounds by $\;v\;$

  • $f(u,0)=27(3-2u)^2\ge0,$
  • $f\left(u,\dfrac{u^2}4\right)=\dfrac3{16}(1296-1728u+648u^2+48u^3-79u^4+16u^5-u^6)$ $=\dfrac3{16}(9-u^2)(u^2-8u+12)^2\ge0.$

At the stationary points $$2f(u,v)=2f(u,v)-v\,f'_v(u,v)=g(u,v),$$ where

  • $g(u,v)=486-648u+216u^2+(54+36u-60u^2+10u^3)v,$
  • $g(u,0)=54(3-2u)^2\ge0,$
  • $g\left(u,\dfrac{u^2}4\right)=\dfrac12(972-1296u+459u^2+18u^3-30u^4+5u^5)$ $=\dfrac52\left(u+\dfrac{58}{15}\right)\left(u-\dfrac85\right)^2\left(u-\dfrac{10}3\right)^2 +\dfrac{253}{15}\left(u+3\right)\left(u-\dfrac53\right)^2$ $+\dfrac1{1350}\left(95150-119630u+38207u^2\right)\ge0.$

Since $\;g(u,v)\;$ is a linear function by $\;v,\;$ it achives the least value at the edges of the area.

Proved!

$\endgroup$
17
  • 2
    $\begingroup$ Why offtopic? I think your solution is wrong. You said "$2p^3+3p^2-1=(p+1)^2(2p-1)\ge 0,\quad p\ge\dfrac12$", it should be $2p^3+3p^2-1 \le 0$. You make a mistake $2p^3+3p^2-1 \ge 0$. $\endgroup$
    – River Li
    Mar 8 at 3:34
  • 1
    $\begingroup$ How is this "neater" and "nicer" than the solution provided by OP? $\endgroup$
    – V.S.e.H.
    Mar 14 at 12:45
  • 1
    $\begingroup$ @YuriNegometyanov Check: $4p-5r=5xy(3-x-y)-4\big(xy+(x+y)(3-x-y)\big)$. $\endgroup$
    – River Li
    Mar 14 at 14:10
  • 1
    $\begingroup$ @YuriNegometyanov $4p\ge 5r-11$ is incorrect, e.g., for $x = 0, y = z = 3/2$. Or $x = 1/100, y = z = 299/200$. $\endgroup$
    – River Li
    Mar 14 at 14:23
  • 1
    $\begingroup$ @YuriNegometyanov Sorry, it is still incorrect. $4(27-6r+3p)^2+49p^2-(12r-11p)^2 = 12(-3p^2+10pr+54p-108r+243)$ is wrong. E.g., for $x = y = z = 1$ (so $s = 3, r = 3, p = 1$), we have $4(27-6r+3p)^2+49p^2-(12r-11p)^2 = 0$, however, $12(-3p^2+10pr+54p-108r+243) = 576$. $\endgroup$
    – River Li
    Mar 15 at 0:57

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.